A calculus problem by Rocco Dalto

Calculus Level pending

The solution to the differential 1 2 ( d y d x ) 2 a y = 1 2 \dfrac{1}{2} \left(\dfrac{dy}{dx}\right)^2 - \dfrac{a}{y} = \dfrac{1}{2} can be expressed as the arc x = f ( θ ) x = f(\theta) , y = g ( θ ) y = g(\theta) , and the curve passes thru the origin so that x = y = 0 x = y = 0 , when θ = 0 \theta = 0 .

The volume formed by rotating the above curve x = f ( θ ) x = f(\theta) , y = g ( θ ) y = g(\theta) about the x x -axis from θ = 0 \theta = 0 to θ = ln ( 2 ) \theta = \ln(2) can be expressed as ( m n p q ln ( q ) ) a 3 π (\dfrac{m}{n} - \dfrac{p}{q} * \ln(q)) * a^3\pi , where ( m , n ) (m,n) and ( p , q ) (p, q) are pairs of coprime positive integers.

Find: m + n + p + q . m + n + p + q.

Refer to previous problem. . .


The answer is 182.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Nov 22, 2016

1 2 ( d y d x ) 2 a y = 1 2 \dfrac{1}{2} * (\dfrac{dy}{dx})^2 - \dfrac{a}{y} = \dfrac{1}{2} \implies

d y d x = 2 a + y y x = y 2 a + y d y \dfrac{dy}{dx} = \sqrt{\dfrac{2a + y}{y}} \implies x = \int \sqrt{\dfrac{y}{2a + y}} \: dy

Let u 2 = y 2 u d u = d y u^2 = y \implies 2u \: du = dy \implies

x = 2 u 2 2 a + u 2 d u x = 2 * \int \dfrac{u^2}{\sqrt{2a + u^2}} \: du

Let u = 2 a s i n h ( θ ) d u = 2 a c o s h ( θ ) d θ u = \sqrt{2a} sinh(\theta) \implies du = \sqrt{2a} cosh(\theta) \: d\theta \implies

x = 2 a ( c o s h ( 2 θ ) 1 ) d θ = 2 a ( 1 2 s i n h ( 2 θ ) θ ) ) = a ( s i n h ( 2 θ ) 2 θ ) + C . x = 2a * \int (cosh(2\theta) - 1) \: d\theta = 2a * (\dfrac{1}{2} sinh(2\theta) - \theta)) = a * (sinh(2\theta) - 2\theta) + C.

x ( θ ) = 0 C = 0 X = a ( s i n h ( 2 θ ) 2 θ ) ) x(\theta) = 0 \implies C = 0 \implies X = a * (sinh(2\theta) - 2\theta))

x = u 2 = 2 a s i n h 2 ( θ ) = a ( c o s h ( 2 θ ) 1 ) . x = u^2 = 2a * sinh^2(\theta) = a * (cosh(2\theta) - 1).

Replacing 2 θ 2\theta by θ \theta we obtain:

x = a ( s i n h ( θ ) θ ) x = a * (sinh(\theta) - \theta) , y = a ( c o s h ( θ ) 1 ) y = a * (cosh(\theta) - 1)

Now we rotate the curve about the x - axis from θ = 0 \theta = 0 to θ = ln ( 2 ) \theta = \ln(2) .

The Volume V = π 0 ln ( 2 ) ( y ( θ ) ) 2 d x d θ d θ V = \pi \int_{0}^{\ln(2)} (y(\theta))^2 \dfrac{dx}{d\theta} \: d\theta

a 3 π 0 ln ( 2 ) ( c o s h ( θ ) 1 ) 3 d θ = a^3\pi * \int_{0}^{\ln(2)} (cosh(\theta) - 1)^3 \:d\theta =

a 3 π 0 ln ( 2 ) ( c o s h 3 ( θ ) 3 c o s h 2 ( θ ) + 3 c o s h ( θ ) 1 ) d θ = a^3\pi * \int_{0}^{\ln(2)} (cosh^3(\theta) - 3cosh^2(\theta) + 3cosh(\theta) - 1) \: d\theta =

a 3 π 0 ln ( 2 ) ( ( 1 + s i n h 2 ( θ ) ) c o s h ( θ ) 3 2 ( c o s h ( 2 θ ) + 1 ) + 3 c o s h ( θ ) 1 ) d θ = a^3\pi * \int_{0}^{\ln(2)} ((1 + sinh^2(\theta)) cosh(\theta) - \dfrac{3}{2} (cosh(2\theta) + 1) + 3 cosh(\theta) - 1) \: d\theta =

a 3 π 0 ln ( 2 ) ( 4 c o s h ( θ ) + s i n h 2 ( θ ) c o s h ( θ ) 3 2 c o s h ( θ ) 5 2 ) d θ = a^3\pi * \int_{0}^{\ln(2)} (4 cosh(\theta) + sinh^2(\theta) * cosh(\theta) -\dfrac{3}{2} cosh(\theta) - \dfrac{5}{2}) \: d\theta =

a 3 π ( 4 s i n h ( θ ) + s i n h 3 ( θ ) 3 3 4 s i n h ( 2 θ ) 5 2 ) 0 ln ( 2 ) = a^3\pi * (4 sinh(\theta) + \dfrac{sinh^3(\theta)}{3} - \dfrac{3}{4} sinh(2\theta) - \dfrac{5}{2})|_{0}^{\ln(2)} =

a 3 π ( 3 + 9 64 45 32 5 2 ln ( 2 ) ) = a^3\pi * (3 + \dfrac{9}{64} - \dfrac{45}{32} - \dfrac{5}{2} \ln(2)) =

a 3 π ( 111 64 5 2 ln ( 2 ) ) = a 3 π ( m n p q ln ( q ) ) a^3\pi * (\dfrac{111}{64} - \dfrac{5}{2} \ln(2)) = a^3\pi * (\dfrac{m}{n} - \dfrac{p}{q} * \ln(q))

m + n + p + q = 182. \implies m + n + p + q = 182.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...